Identification of the formation of resonant tones in compressible cavity flows - Bacci, David; Saddington, Alistair J.; Bray, Derek (Elsevier, 2018)
Identification of the fluid dynamic mechanisms responsible for the formation of resonant tones in a cavity flow is challenging. Time-frequency non-linear analysis techniques were applied to the post-processing of pressure signals recorded on the floor of a rectangular cavity at a transonic Mach number. The results obtained, confirmed that the resonant peaks in the spectrum were produced by the interaction of a carrier frequency (and its harmonics) and a modulating frequency. High-order spectral analysis, based on the instantaneous wavelet bi-coherence method, was able to identify, at individual samples in the pressure–time signal, that the interaction between the fundamental frequency and the amplitude modulation frequency was responsible for the creation of the Rossier–Heller tones. The same technique was also able to correlate the mode switching phenomenon, as well as the deactivation of the resonant tones during the temporal evolution of the signal.